The Impact of Mobility Policy and Modal Share to The University Community in Bologna - Battistini, Roberto; Sacchetti, Luciana; Braschi, Andrea (Universitas Diponegoro, 2021)
In the Twentieth century transportation has been one of the most impactful drivers for economic and social development, while nowadays, it appears as a major cause of environmental and social problems. Even worse, the more transportation has become a relevant part in daily life and business, the more it is blamed for problems such as traffic congestion, car accidents, social economic inequality, energy consumption and pollution. Transportation is in fact caught in a vicious circle. Urban planning is forced to reduce transition costs, transforming cities in a sort of social network, and in parallel to orient mobility towards sustainability, both capable to convey socioeconomic development. Within this context, the University of Bologna has chosen a sustainable approach for its Multi-campus territorial structure, applying several sustainable mobility policies regarding public transportation, cycling, electric/hybrid car fleet and walking accessibility. The paper purpose is to show significative links between sustainable policy application and modal share, using data from an online survey submitted to university staff and students. Even gender influence on modal share has been investigated.